If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(4g+6)=2g(6g+9)
We move all terms to the left:
3(4g+6)-(2g(6g+9))=0
We multiply parentheses
12g-(2g(6g+9))+18=0
We calculate terms in parentheses: -(2g(6g+9)), so:We get rid of parentheses
2g(6g+9)
We multiply parentheses
12g^2+18g
Back to the equation:
-(12g^2+18g)
-12g^2+12g-18g+18=0
We add all the numbers together, and all the variables
-12g^2-6g+18=0
a = -12; b = -6; c = +18;
Δ = b2-4ac
Δ = -62-4·(-12)·18
Δ = 900
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$g_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$g_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{900}=30$$g_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-6)-30}{2*-12}=\frac{-24}{-24} =1 $$g_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-6)+30}{2*-12}=\frac{36}{-24} =-1+1/2 $
| 2x=-3x+36 | | -2+3n-2=9n+8 | | 3(k-5)=6(k-2) | | 5+2y=-13+2y5+2y=−13+2y | | 11=y-(-4)^2 | | (5x+8)+(6x+8)+82=180 | | 6a-12=4a+4 | | 6x-84=x | | -2a+14=-3(5a+4) | | 48-3/8-1/3=r | | 5x+12=3x+48* | | 2/3-5/6x=4/9 | | 192=w(3w) | | 10(v+7)=210 | | (5x+8)+(6x+8)=82 | | 192=w(3) | | 5v+4-2(-8v-3)=3(v-2) | | 8+2=3b+12 | | 10=-3y+5.8 | | -3k=-6k+9 | | -5y=-16 | | 4(x+1)=7x-5 | | –14+11t=9t | | -12-2=x-5 | | -10=4(v+5)-7v | | 3n =15 | | 2/5(5/2k)=2/5(-10) | | -2/3x=-2/9 | | 3x+26=16x4 | | x-2=16-18 | | 26+3x=16x | | -10=4(v=5)=7v |